2013
DOI: 10.1186/1471-244x-13-185
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of factors influencing conditional discharge from a forensic hospital: the DUNDRUM-3 programme completion and DUNDRUM-4 recovery structured professional judgement instruments and risk

Abstract: BackgroundWe set out to examine whether structured professional judgement instruments DUNDRUM-3 programme completion (D-3) and DUNDRUM-4 recovery (D-4) scales along with measures of risk, mental state and global function could distinguish between those forensic patients detained in a secure forensic hospital (not guilty by reason of insanity or unfit to stand trial) who were subsequently discharged by a mental health review board. We also examined the interaction between these measures and risk, need for thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 20 publications
6
75
0
Order By: Relevance
“…Davoren et al (2015) also found that a higher DUNDRUM-1 triage security score predicted a longer LOS. Lower (better) scores in the DUNDRUM-3 program completion and DUNDRUM-4 recovery scores predicted moves to less secure settings (Davoren et al, 2012) and conditional discharge to the community (Davoren et al, 2013) as did the HCR-20 dynamic scales. Another Dutch study found that patients in LFPC are more often recidivists than patients in RFPC ( Van der Kraan, Schekman, Nijman, Hulsbos, & Bulten, 2008) which aligns with the present findings.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Davoren et al (2015) also found that a higher DUNDRUM-1 triage security score predicted a longer LOS. Lower (better) scores in the DUNDRUM-3 program completion and DUNDRUM-4 recovery scores predicted moves to less secure settings (Davoren et al, 2012) and conditional discharge to the community (Davoren et al, 2013) as did the HCR-20 dynamic scales. Another Dutch study found that patients in LFPC are more often recidivists than patients in RFPC ( Van der Kraan, Schekman, Nijman, Hulsbos, & Bulten, 2008) which aligns with the present findings.…”
Section: Discussionmentioning
confidence: 91%
“…Validation studies have shown good psychometric qualities (Flynn, O'Neill, McInerney, & Kennedy, 2011;Freestone et al, 2015;O'Dwyer et al, 2011) and indicated that the DUNDRUM-1 items can predict the level of therapeutic security needed (Flynn et al, 2011;Freestone et al, 2015) and LOS (Davoren et al, 2015) while the DUNDRUM-3 and DUNDRUM-4 can predict moves between levels of therapeutic security (Davoren et al, 2012) and discharge (Davoren et al, 2013).…”
Section: Dangerousness Understanding Recovery and Urgency Manual (Thmentioning
confidence: 99%
“…These studies demonstrate that with regards to demographic factors, reassuringly, neither ethnicity nor age are associated with outcome at tribunal [13, 14, 1721]. The role of patient sex is unclear; trend-level associations reported in samples of both civil and forensic patients in both the UK and New Zealand indicate that females are more likely to be discharged than males [6, 13, 22]; however, the only previous study to have found a significant association between sex and outcome reported that males are more likely to receive discharge at tribunal than females [17].…”
Section: Introductionmentioning
confidence: 97%
“…The role of patient sex is unclear; trend-level associations reported in samples of both civil and forensic patients in both the UK and New Zealand indicate that females are more likely to be discharged than males [6, 13, 22]; however, the only previous study to have found a significant association between sex and outcome reported that males are more likely to receive discharge at tribunal than females [17]. Findings with regard to diagnosis are also mixed, Dibben and colleagues reported that when compared to patients with schizophrenia, those with mania were five times more likely to be discharged by the tribunal [23], yet other studies have observed that neither mental disorder [17, 20, 21] nor personality disorder [18] are related to outcome at MHRT. Perhaps unsurprisingly, a study conducted in a sample of maximum security inpatients in Canada reported that patients with higher psychopathy scores were significantly less likely to be discharged than those with lower scores [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation